10 Digital Technology for Business World 2019 - Waiwanijchakij, Pairoj (Journal of Digital Communications, 2019)
Today advancement of various Digital Technology creates a big impact to people’s lifestyle and way of business, resulting in new business emerging and requirement for new generation of skilled professional. This article is written to extend a report of Gartner Inc. on 10 Digital Technology Trend in 2019 that impact to worldwide industries. They are categorized into 4 groups : Intelligent, Digital, Mesh and supporting technologies. The paper will help reader to understand and aware to cope with the development of these technologies in personal life and business direction.